Shock Simulation Day: Medical Decision-Making and Communication Skills for Managing a Hypotensive Adult in a Rapid Response - A. Vincent Raikhel; Alexandra C. Collis; David Carlbom (Association of American Medical Colleges, 2024)
Introduction Shock is a life-threatening condition amongst hospitalized patients and requires urgent management to avoid mortality. Early exposure is vital for educational and patient safety purposes. Methods We developed a 90-minute shock day session that provided internal medicine interns with a cognitive framework for the initial diagnosis and management of shock, which they applied to two simulations. The first simulation involved a patient with septic shock, and the second involved a patient with cardiogenic shock. Critical action checklists were used to assess learners and guide structured debriefs after each simulation. Medical decision-making and communication frameworks were presented through a presession video and a chalk talk. The curriculum was evaluated using pre- and postintervention surveys to assess knowledge and confidence. Results Forty-eight interns participated in the session in 2022 and 2023. We observed an increase in the percentage of learners correctly answering a knowledge-based question regarding the amount of fluid administered to a patient in septic shock (pre: 33%, post: 62%, p < .01), as well as increases in learner-reported confidence in leading a rapid response (pre: 9%, post: 62%) and in managing undifferentiated shock (pre: 13%, post: 56%), septic shock (pre: 20%, post: 83%), cardiogenic shock (pre: 2%, post: 54%), hemorrhagic shock (pre: 20%, post: 73%), and anaphylactic shock (pre: 22%, post: 54%, all ps < .01). Discussion Employing a variety of pedagogical methods, we demonstrated that intern knowledge and confidence regarding the management of a hypotensive patient during a rapid response can be increased through participation in our curriculum.